MANAJEMEN TENAGA PENDIDIK DALAM MENJAGA MUTU PEMBELAJARAN AL-QUR’AN DI PONDOK PESANTREN IMAM SYAFI’I NASHIRUSSUNNAH - Gerhana; Akhmad Shunhaji; Agus Tasbih (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the management of teaching staff in maintaining the quality of Al-Qur’an learning at Imam Syafi’i Nashirussunnah Islamic Boarding School. The research employed a qualitative method with a descriptive approach, utilizing data collection techniques including observation, interviews, and documentation.The findings indicate that the management of teaching staff—encompassing planning, recruitment, development, and evaluation—plays a significant role in sustaining the quality of Al-Qur’an learning within an educational institution. Needs-based planning contributes to the provision of educators who meet the required competency standards, while selective recruitment ensures the initial quality of teachers. Continuous professional development has been shown to enhance both pedagogical and professional competencies, whereas consistent evaluation functions to maintain learning quality standards. However, several challenges remain, particularly in the systematization of recruitment processes, teacher welfare, and the optimization of performance evaluation. Therefore, strengthening a more structured and sustainable teaching staff management system is essential to improve the quality of Al-Qur’an learning effectively.